2003
DOI: 10.1002/pros.10331
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor effect of combination therapy with intratumoral controlled‐release paclitaxel (PACLIMER® microspheres) and radiation

Abstract: A controlled-release formulation of paclitaxel can be very effective in the treatment of prostate cancer. Additionally, PACLIMER Microspheres may be effectively used as a radiosensitizer in genitourinary cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…Treatment of the xenografts with intratumoral Paclimer® alone significantly decreased tumor size compared to controls, and showed synergistic activity when combined with radiation therapy (35). This effect has also been observed by our group in intracranial 9L gliosarcomas in rats using a combination of Paclimer® and radiation therapy (36).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Treatment of the xenografts with intratumoral Paclimer® alone significantly decreased tumor size compared to controls, and showed synergistic activity when combined with radiation therapy (35). This effect has also been observed by our group in intracranial 9L gliosarcomas in rats using a combination of Paclimer® and radiation therapy (36).…”
Section: Discussionsupporting
confidence: 79%
“…Paclimer® has also demonstrated beneficial effects against human prostate tumors implanted in nude mice (35). Treatment of the xenografts with intratumoral Paclimer® alone significantly decreased tumor size compared to controls, and showed synergistic activity when combined with radiation therapy (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paclitaxel is one of a few chemotherapeutic agents that is effective in patients with advanced prostate cancer (14,15). Studies using prostate-specific antigen response as an end point showed the efficacy of paclitaxel in the treatment of metastatic prostate cancer (16 -18).…”
mentioning
confidence: 99%
“…Treatment of patients with paclitaxel alone or in combination with estramustine resulted in a >50% decrease in serum prostate-specific antigen in 40% to 60% of the treated patients (16 -18). Unfortunately, patients treated with paclitaxel or other chemotherapeutic drugs experience significant systemic side effects that include neutropenia, mucositis, neurotoxicity, and gastrointestinal effects (15,17,18). These adverse effects severely limit the duration and dose of drug treatment that can be administered (14,18).…”
mentioning
confidence: 99%